ANALYZING THE CORRELATION BETWEEN DEALING WITH STRESS AND SELF-ESTEEM OF THE PARTICIPANT WHO ARE 25 YEARS OLD AND YOUNGER - Erdogan, B. S.; Sahın, A.; Aldemır, GY; Eravsar, H; Bıngol, E; Fılız, K; Şahan, H; Yıldız M (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
The aim of the study is to investigate the correlation between the attitudes of young people who do sports and their self-esteem. The research group included 83 men and 117 women ( age=21,49 + 1,659), as a total 200, who make exercises at least 1 year in special gym center in Antalya and Konya . Self-esteem scale developed by Arıcak [2] and Dealing with Stress Scales developed by Özbay [20] were used to reach the aim of the study. Meaningfulness was acquired as P<0,05 by using Kolmogorov-Smirnov test, t testand Pearson Correlation while commenting on the data. SPSS (Statistical package for social sciences) programme was used to evaluate the data. At the end of the research meaningful and direct correlation was acquired .01 (P<0,01) between sub dimensions active planning of dealing with stress and value of ego (r=497), self- confident (r=577), depressive emotion (r=531), self-sufficiency (r=572), succsess and productivity (r=476). As a general result different attitudes to cope with the stress were seen in the youth participants because of their gender's characteristics and it was thought that the correlation between those attitudes and their self -esteem was at the medium and higher-up level. Exercise helps people maintaining their social lives make them develop their levels to deal with the stress. When the other researches were examined in the literature, the results were parallel with each other.Yeltepe and Yargıç [30].